UTILIZATION OF MICROWAVES FREQUENCY FOR IDENTIFICATION OF CERVIX AND OVARIUM CANCER TISSUE IN INTRAOPERATIVE CONSULTATION PROCESS - Dinulhaq, Faris
Cancer is a disease caused by cell proliferation abnormalities. One of the methods that can be used to overcome this disease is by removing the cancerous tissue. Identification of cancer tissue in the operation stage (intraoperative consultation) is an important stage for the surgeon to determine the next action. Until now, tissue identification in intraoperative consultation is still done manually using cryosection methods. The cryosection method is reported to have fairly good accuracy in the identification of cancerous tissue. However, the accuracy of this method is very dependent on the experience and skill of the doctors, so this method is very vulnerable to human error. To overcome this problem, a standardized identification method for a cancer tissue in intraoperative consultation is needed to reduce the human error. The development of cancer identification methods by using tissue permittivity at microwave frequencies in recent years has shown quite promising results. This is because the measurement of tissue permittivity using microwave frequencies can be performed several times without damaging the samples. In addition, several studies on several types of cancer showed differences in tissue permittivity between cancerous and normal tissue. Until now there are no studies that report the application of this method, especially for intraoperative consultation for cervix and ovarian cancer. To answer the problem, this study aims to create and test the tool that been made that can distinguish cancerous and normal tissue based on the tissue permittivity value using microwaves frequencies. Besides being able to minimize human error, the device is designed to be portable and able to provide diagnostic results faster than the cryosection method. The initial stage of this research is the production of the tools. The device that has been made is then tested for the ability to differentiate tissue based on water content parameters and tissue type before measuring cancer samples. Measurements are made every 0,002 GHz in the microwave frequency ranging from 8,2 to 12,4 GHz or around 2000 measurement points using TE10 measurement method. The measurement results then processed using the TPS (transmission phase shift) method to determine the permittivity value. The next stage is the measurement of cervix (n=13) and ovarian tissue samples (n=12) obtained from Hasan Sadikin Hospital (RSHS) Bandung. The tissue obtained was identified by RSHS medical doctor diagnosis. Fresh sample from the surgery is then measured in less than 2 hours. The permittivity values of each tissue are then compared and their significance is tested using statistical analysis. The tool that designed was successfully made in a relatively smaller dimension (6,28 x 23,5 x 2,11 cm) that made this tool portable. Measurement of tissue samples using this tool is done within ± 5 minutes from sample preparation until the results came out, so this tool can analyze tissue samples faster than the cryosection method which generally takes ± 20 minutes. The results of water content parameters measurement showed fresh leaves that contained more water have a bigger permittivity value than dry leaves, additional liquid to the sample also showed an increase of permittivity. Various tissue type testing showed that ligament tissue has bigger permittivity than the other tissue. Permittivity measurement of tissue samples from RSHS showed that healthy cervix has a permittivity value of 1,84 ± 0,28 while cervical cancer has 1,60 ± 0,3, or it can be said that healthy tissue has 12,95% bigger permittivity value than cancerous tissue at 8,71 GHz (p < 0,05). While in ovarian tissue, the permittivity value of cancer is 3,27 ± 0,40 and healthy tissue is 2,91 ± 0,01, or it can be said that cancer has a 10,95% bigger permittivity value than healthy tissue at 11,82 GHz (p <0,05). The permittivity difference in leaves permittivity is caused by differences in water content treatment. Increased water content in biological material causes an increase in permittivity values. The difference in tissue types can also cause differences in permittivity measured, as shown from the difference in ligament permittivity compared to meat and liver tissue. The difference in permittivity between cancer and normal tissue is thought to be due to changes in the metabolic profile and water content of cancer tissue. Changes in metabolism that occur cause differences in the profile of proteins and molecules in cancer cells with normal cells. The metabolic difference may affect permittivity value. Increased water content in cancer tissue may also affect the permittivity. Results of the histological assay on samples exposed to microwaves showed no damage on tissue. This is because the microwaves used in this method is considered safe for humans. Based on the results of this study, it can be concluded that microwaves frequency can be used to distinguish ovarian and cervical cancer tissue from healthy tissue. So, this method has the potential to be a new method for cancer tissue identification in intra-operative consultation